Peran pendidikan islam dalam mengatasi krisis moral generasi z di era digital - Amelia, Silvi (Maliki Interdisciplinary Journal, 2026)
The moral crisis affecting Generation Z in the digital era is a complex phenomenon influenced by rapid technological advancement, globalization, and the weakening internalization of moral and spiritual values. While the digital environment provides broad access to information, it also poses serious challenges to the moral development of young generations due to cultural exposure that may conflict with local ethical norms. This article aims to analyze the moral crisis experienced by Generation Z and examine the strategic role of Islamic education as a solution to this issue This study employed a qualitative method with a library research approach through the analysis of various relevant primary and secondary literature sources. The findings indicate that Islamic education plays an important role in shaping akhlaqul karimah by instilling values such as honesty, responsibility, tolerance, and digital ethics. Although Islamic education in the digital era faces various challenges, including the misuse of technology and the rapid flow of information, these challenges can be addressed through the integration of character education, the strengthening of digital literacy, and collaboration among schools, families, and communities. Therefore, Islamic education has the potential to become a holistic solution in shaping Generation Z into individuals who possess integrity, noble character, and the ability to face global challenges without losing their moral and spiritual identity.